Pengaruh Green Accounting, Capital Adequacy Ratio Dan Cash Flow Risk Management Practices Terhadap Financial Sustainability - Nandia Ifani Candrasari; Etty Murwaningsari (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2024)
Purpose – This research aims to examine the relationship between financialsustainability and green accounting, capital adequacy ratio, and to see howcash flow risk management practices in companies, especially banks, willinfluence banking financial sustainability.Design/methodology/approach – This method used in this study usesquantitatives methods by sampling using purposive sampling techniqueswith the result of 40 banks listed on the Indonesia Stock Exchange (BEI) thatpresents and publishes annual reports and sustainability reports for theperiod 2020 to 2022. The data used is secondary data, namely data obtaineddirectly in the form of financial statement and sustainability report fromwww.idx.com sites and their respective company websites which are used asresearch samples. Data analysis techniques are carried out using statisticalanalysis, namely: classical assumption tests (normality, multicollinearity,heterokedasticity, and autocorrelation), multiple linear analysis, andhypothesis tests, as well as coefficients of determination with SPSS 25.0 forwindow.Findings – Based on the results of the study, it was found that FinancialSustainability is positively influenced by green accounting, cash flow riskmanagement practices on operating activities, and cash flow riskmanagement practices on financing activities. Meanwhile, capital adequacyratio and cash flow risk management practices on investing activities do nothave a positive influence on financial sustainability.Research limitations/implications – For the conclusions that have beenput forward, researchers can provide some suggestions for improving thequality of further research. The suggestions proposed by the researcherinclude adding the number of other variables that are expected to affect thefinancial sustainabiluty, then the company is advised to pay attention to thefactors that affect its financial sustainability.